Ban on the Burning of Solid Fuels in Domestic Furnaces and its Impact on Air Quality – Example of Krakow - Kicińska, Alicja; Jawdyńska, Julia (Archives of Mining Sciences, 2025)
The present study assessed the effectiveness of the ban on the burning of solid fuels in domestic furnaces imposed in Krakow, a city of almost one million people, to reduce particulate emissions. The assessment was carried out based on the database of the Inspectorates for Environmental Protection using data on air concentrations of PM2.5, PM10, NO2, SO2, O3 and B[a]P. Our analysis showed that between 2010 and 2021, the annual average concentrations of PM10, PM2.5, NO2, SO2 and B[a]P in Krakow decreased by 42%, 40%, 6%, 50% and 60%, respectively, while the annual mean ozone concentration in the city increased by 21.2%. The largest decreases in air concentrations of PM10 (56%), PM2.5 (55%), B[a]P (71%) and SO2 (75%) were seen in heating seasons. A significant finding from our study was that, as a result of the measures taken, the annual mean concentrations of SO2 and NO2 in Krakow did not exceed the legal limit values for the pollutants in any of the years analysed and that the legal limit value for the annual mean concentration of PM10 was not exceeded since 2019. A negative finding was that the limit/target values for PM2.5, B[a]P and the maximum daily 8-hour mean ozone concentration were not met. Although an anti-smog resolution was implemented in Krakow, the air quality during the analysed period remained poor, particularly in heating seasons, and the goals for reducing pollutant emissions were not achieved. However, while the objectives for reduction in PM10, PM2.5 and B[a]P emissions were not met, the reductions in emission levels achieved in Krakow were significantly better than those seen for the entire Małopolska Province. This undoubtedly results from the gradual reduction in the number of solid fuel furnaces and boilers in Krakow, which in turn led to large reductions in particulate and B[a]P emissions from the municipal and residential sectors. Our analyses showed that while the measures taken yielded good results, it is necessary to introduce other solutions to further reduce air pollution in the city.
Keywords: Agglomeration; air pollution; particulate matter; anti-smog resolutions; low-height emissions